Bon Bon's Enterprise / Maryumah Che Abdullah... [et. al] - Che Abdullah, Maryumah; Haris, Mohd Zul Halili; Mohd Jefry, Nurfazliana; Zarnudin, Zailina (2012)
Bon Bon’s Enterprise is our company names that we planned to become the symbols and proud of our partnership that can satisfies our customer needs. Our company produce Bon Bon’s chocolates to our customer so that they can enjoy it with their family. Each partner needs to contribute RM 33,703.50 and it turns our capital for this business isRM 134,814.00. This partnership business owned byMohd Zul Halili bin Haris, Maryumah binti Che Abdullah, Nurfazliana binti Mohd Jefry and Zailina binti Zarnudin. Our business location are located around Bandar Perda, Penang.. This business will serve a Brazilian styleBon Bon’s chocolate which use only three ingredients however still can give our customer a health benefit physically and emotionally. There is no companies has sell this product and we are the first one. Based on our competitive analysis, our business will successful soon. We hope our business can joy the customer starting age from child until adult.